The Microbial Metabolite Butyrate Induces Expression of Th1-Associated Factors in CD4+ T Cells - Kespohl, Meike; Vachharajani, Niyati; Luu, Maik; Harb, Hani; Pautz, Sabine; Wolff, Svenja; Sillner, Nina; Walker, Alesia; Schmitt-Kopplin, Philippe; Boettger, Thomas; Renz, Harald; Offermanns, Stefan; et al. (Frontiers in Immunology, 2017)
Short-chain fatty acids (SCFAs), which are generated by the bacterial fermentation of dietary fibers, promote expansion of regulatory T cells (Tregs). Potential therapeutic value of SCFAs has been recently highlighted in the experimental models of T cell-mediated autoimmunity and allergic inflammation. These studies suggest that physiological intestinal concentrations of SCFAs within the millimolar range are crucial for dampening inflammation-mediated processes. Here, we describe opposing effects of SCFAs on T cell-mediated immune responses. In accordance with published data, lower butyrate concentrations facilitated differentiation of Tregs in vitro and in vivo under steady-state conditions. In contrast, higher concentrations of butyrate induced expression of the transcription factor T-bet in all investigated T cell subsets resulting in IFN-g-producing Tregs or conventional T cells. This effect was mediated by the inhibition of histone deacetylase (HDAC) activity and was independent of SCFA-receptors FFA2 and FFA3 as well as of Na+-coupled SCFA transporter Slc5a8. Importantly, while butyrate was not able to induce the generation of Tregs in the absence of TGF-b1, the expression of T-bet and IFN-g was triggered upon stimulation of CD4+ T cells with this SCFA alone. Moreover, the treatment of germ-free (GF) mice with butyrate enhanced the expression of T-bet and IFN-g during acute colitis. Our data reveal that, depending on its concentration and immunological milieu, butyrate may exert either beneficial or detrimental effects on the mucosal immune system.